Addressing Sexual Violence: The Reality and Strategies of Female Ojek (Motorbike Ride Service) Drivers in Banyumas Regency - Noer Anissa Rakhmawati; Soetji Lestari; Tyas Retno Wulan (Pusat Studi Gender dan Anak (PSGA) IAIN Purwokerto, 2024)
The emergence of the phenomenon of female online motorcycle taxi drivers in the Banyumas district shows that women’s emancipation has taken place. Transportation has become a daily need for Banyumas residents, this is used by some women to earn a living. However, in the field, there are quite a few who experience sexual violence, including touching drivers’ body parts, sexual chats, invitations to perform sexual acts, and attaching male vital parts to female online motorcycle taxi drivers. There are several strategies used by female online motorcycle taxi drivers, namely communicating well, reprimanding consumers with kind words, and threatening to report them to the online motorcycle taxi driver.